2018
DOI: 10.1186/s13229-018-0233-5
|View full text |Cite
|
Sign up to set email alerts
|

Links between looking and speaking in autism and first-degree relatives: insights into the expression of genetic liability to autism

Abstract: BackgroundRapid automatized naming (RAN; naming of familiar items presented in an array) is a task that taps fundamental neurocognitive processes that are affected in a number of complex psychiatric conditions. Deficits in RAN have been repeatedly observed in autism spectrum disorder (ASD), and also among first-degree relatives, suggesting that RAN may tap features that index genetic liability to ASD. This study used eye tracking to examine neurocognitive mechanisms related to RAN performance in ASD and first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
81
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(95 citation statements)
references
References 70 publications
12
81
2
Order By: Relevance
“…Interestingly, the pattern of reduced mean and increased range of F0 was driven by females with the BAP. While evidence of clear sex-specific differences in the expression of the BAP is limited (Rubenstein and Chawla 2018;Sasson et al 2014;Seidman et al 2012), recent work has demonstrated stronger associations between mothers with the BAP and their children on measures of language fluency compared to fathers with the BAP (Nayar et al 2018). Results from the present study add to such evidence, perhaps suggesting a stronger maternal effect in the language-related phenotypes reflecting genetic liability to ASD.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Interestingly, the pattern of reduced mean and increased range of F0 was driven by females with the BAP. While evidence of clear sex-specific differences in the expression of the BAP is limited (Rubenstein and Chawla 2018;Sasson et al 2014;Seidman et al 2012), recent work has demonstrated stronger associations between mothers with the BAP and their children on measures of language fluency compared to fathers with the BAP (Nayar et al 2018). Results from the present study add to such evidence, perhaps suggesting a stronger maternal effect in the language-related phenotypes reflecting genetic liability to ASD.…”
Section: Discussionsupporting
confidence: 53%
“…Such phenotypes are thought to reflect underlying genetic liability, and might afford better understanding of the range of phenotypic expression of ASD liability, and links to underlying biology. To this end, prior studies have shown a specific neuropsychological profile associated with the BAP in parents of individuals with ASD, where differences in social cognition and language processing abilities were evident in the subgroup of parents showing BAP features, whereas those without these subclinical phenotypes performed more similarly to controls (e.g., Losh et al 2009;Nayar et al 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, maternal pragmatic language scores were strongly associated with children's social and nonverbal communication skills measured by the ADI-R. Similar parent-child associations have been observed in other studies examining language-related phenotypes, where subtle differences in language fluency in mothers with the BAP were found to relate to more severe symptoms in their children with ASD 19 . Such a pattern of lineality may suggest a stronger inherited maternal effect for language-related phenotypes in ASD (though important to consider is that parents and children influence one another's language patterns as well).…”
Section: Discussionsupporting
confidence: 81%
“…ASD symptomatology in children has also been shown to correlate with BAP features in parents [14][15][16] , even when BAP traits were noted before a parent went on to have a child with ASD 17 . Further, BAP features have been shown to cosegregate with distinct patterns of neurocognitive performance in clinically unaffected relatives 12,[18][19][20][21][22] , suggesting links with underlying neural substrates impacted by ASD genetic risk. Finally, unlike ASD, which by definition requires the presence of impairments in social interaction and communication, and the presence of restricted and repetitive interests and behaviors, traits of the BAP have been observed to segregate independently in unaffected relatives [22][23][24] , potentially reflecting distinct genetic contributions to the component features of ASD [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Global differences in social communication have been observed among first-degree relatives in other genetically-based disorders impacting language (e.g., specific language impairment; Ruser et al 2007), raising the possibility that differences observed in the ASD parent group overall reflect more general genetic liability to language disorder, rather than ASD specifically. In line with this possibility, a number of prior family studies of ASD have noted broad-based differences from controls among ASD parent groups, with more specific patterns of differences observed among BAP(+) subgroups, including studies of social cognition (Losh et al 2009), face processing (Adolphs et al 2008;Yucel et al 2015), and visual attention during a language processing task (Nayar et al 2018). Future work including comparison groups of parents of children with other genetically-based language disorders will be informative in teasing out ASDspecific risk markers evident in parents.…”
Section: Discussionmentioning
confidence: 90%